Program â€œEARSâ€ Sebagai Upaya Peningkatan Psychological Well Being Pada Masa Pendemi Covid 19 - Farhan Zakariyya; Engkos Kosasih; Lira Fessia Damayanti; Muhammad Ariez Musthofa; Ismawati Kosasih; Riksma Nurahmi Rinalti Akhlan (JURNAL PSIKOLOGI INSIGHT, 2022)
The EARS program is based on the Psychological First Aid (PFA) concept to improve psychological well-being. The program is carried out online using the WhatsApp chat media, training conducted by the helper who received the training. The subjects in this study were adolescents aged 19-25 years who registered and filled out informed consent. Subjects totaling 30 people, but who filled out a total of 13 people in the test so that only 13 people were processed the data. This study uses a quasi-experimental one group pretest and posttest design. Data analysis used paired sample t-test with p 0.05. This shows that the EARS Program can improve psychological well-being.Program EARS disusun berdasarkan konsep Psychological First Aid (PFA) untuk dapat meningkatkan psychological well-being. Program dilakukan secara online dengan menggunakan media chat whatsapp yang dilakukan oleh helper yang mendapatkan pelatihan. Subjek dalam penelitian ini adalah remaja usia 19-25 tahun yang mendaftarkan diri dan mengisi informed consent. Subjek berjumlah 30 orang namun yang mengisi keseluruhan test 13 orang sehingga hanya 13 orang yang diolah datanya. Penelitian ini menggunakan desain kuasi eksperimen one group pretest and posttest design. Analisis data menggunakan paired sample t-test dengan hasil nilai p 0,05. Hal ini menunjukan Program EARS dapat meningkatkan psychological well-being.